Development of Immature CD4+CD8+T Cells Into Mature CD4+ T Cells Requires Alpha-1 Antitrypsin as Observed by Treatment in HIV-1 Infected and Uninfected Controls - Bristow, Cynthia L.; Ferrando-Martinez, Sara; Ruiz-Mateos, Ezequiel; Leal, Manuel; Winston, Ronald (Frontiers in Cell and Developmental Biology, 2019)
Members of the LDL receptor family (LDL-RFMs) interact with human leukocyte elastase on the cell surface (HLE-CS) in complex with the abundant blood protein α1proteinase inhibitor (α1PI, α1-antitrypsin), a process that induces internalization of aggregated functionally-related receptors, including CD4 and the T cell antigen receptor, while simultaneously promoting cellular locomotion. We sought to determine whether augmenting α1PI blood concentration would promote the locomotion of immature T cells through the thymus and generate new CD4+ T cells. Two small clinical trials (NCT01370018, NCT01731691, https://clinicaltrials.gov) were conducted in which HIV-1 infected and uninfected individuals were augmented with α1PI and compared with placebo-treated subjects and untreated controls. Blood cell phenotypes were monitored weekly. We found that CD4/CD8 ratio was significantly increased by α1PI augmentation in both uninfected and HIV-1 infected individuals. We found that maturation of CD4+CD8+ T cells to become immunologically competent CD4+ T cells was regulated by α1PI. We propose a strategy targeting HLE-CS for treating secondary immunodeficiency for which there is currently no direct treatment. Treatment to directly elevate T cells in patients with secondary immunodeficiency, including HIV disease, can be provided by alpha-1 antitrypsin augmentation. Because individuals infected with HIV-1 produce a monoclonal antibody, 3F5, which binds to and inactivates α1PI, a process that prevents α1PI from binding to HLE-CS, thereby blocking locomotion of immature T cells through the thymus to generate CD4+ T cells, we further propose that HIV-1 vaccination should include induction of an antibody that binds to and blocks 3F5 activity, thereby preventing AIDS in addition to the current vaccine strategy for preventing HIV-1 infection. Footnote: Some data from an earlier clinical trial presented herein were previously published in an open-access eBook chapter, “α1Antitrypsin therapy increases CD4+ lymphocytes to normal values in HIV-1 patients.” In: M.Alfano, editors. Soluble factors mediating innate immune responses to HIV infection, Bentham Science Publishers, and are exhibited here in an alternative format for comparison to data from a second, more extensively investigated, previously unpublished clinical trial.